CONCEPT DESIGN SEA CURRENT ENERGY FARMING IN GULF OF KELABAT, BANGKA BELITUNG ISLANDS - Aditya Suwignyo - NIM 155 13 025 , Ignatius
The issue of energy has been a major problem for countries in the world, including Indonesia. Because of that, we have to start developing renewable energy sources which exist in our country, one of them is tidal current energy. The objective of this research is to make a tidal current model in Gulf of Kelabat to locate the potential location that can be made into sea current power plant. Then, this research also determine the instrument that is compatible with the power plant and how much power are generated from it. Lastly, a financial analysis is done to determine the selling price of the generated power. This research use 3D hydrodinamic modeling using Delft3D. In the first step of the modeling process, which is the water face validation in Strait Karimata, the obtained error is 9.335% in 6 different locations. In the second step of the modeling process, which is the sea current validation in Gulf of Kelabat, the obtained error is 30.692% but it shows similarity between model and site measurement in Vx and Vy scatterplot, phase and amplitude of sea current velocity. From the model, the potential location with the biggest sea current velocity is obtained. The location itself is in the waters of Gulf of Kelabat (-1.644 SL, 105.729 EL). The location itself will use 51 Exim TTPP power plants instrument with the amount of generated power up to 740.2 MWh in 2017. In 2018, the implementation of 51 Exim TTPP power plants instrument will need investation about Rp. 184,834,957,638. Because of it, the minimum selling price of the generated power is about Rp. 10,000 for each kWh so the investation can be given back in 25 years.